Into the whirlwind - Martin, Kat (Martin, Kat. BOSS, Inc. novel., 2016)
"A bodyguard, a bounty hunter, a private investigator, no one can handle the heat like the men of BOSS, Inc. Megan O'Brien is at her wit's end. Her three-year-old son has been kidnapped. No police, says the ransom demand. Fearing for her son's life, Meg has no choice but to turn to her former bodyguard, Dirk Reynolds. Dirk's never forgiven Meg for the way she left him after their brief affair. But with bounty hunter Luke Brodie on his side, Dirk knows he's got to help Meg rescue her son. The few clues they've gathered send them spiraling into a murky world of big banking and international crime. Meg may be way out of her depths, but she s seeing a side of Dirk she never suspected one no woman could possibly resist." -- Amazon.com.